Asymmetric Crying Facies in the 22q11.2 Deletion Syndrome: Implications for Future Screening. (December 2013) - Pasick, Christina; McDonald-McGinn, Donna M.; Simbolon, Christine; Low, David; Zackai, Elaine; Jackson, Oksana
Objective. Asymmetric crying facies (ACF) is congenital hypoplasia of the depressor anguli oris muscle characterized by asymmetry of lower lip depression during crying. This has an overall incidence of 0.6%. This study determines the incidence of ACF in a large population of patients with 22q11.2 deletion. Patients and Methods. A retrospective review of medical records on patients with a confirmed 22q11.2 deletion was undertaken. Results . A total of 836 records were reviewed. Of these, 117 (14%) were noted to have ACF on physical examination. Within this latter group, palatal anomalies were common (77%), as was congenital heart disease (78%); however, these numbers did not differ significantly from their known prevalence in the 22q11.2 population. Conclusions. We report a 14% incidence of ACF in patients with a 22q11.2 deletion, significantly higher than in the general population. We suggest, therefore, that newborns with ACF be referred for further screening for the 22q11.2 deletion syndrome.